Human nasal rhinosporidiosis - A case report - S. R, Swarna; V, Stalin Sivagurunathan; T, Bharathi; M, Balamurugan; D, Jeyakumari (Indian Journal of Case Reports, 2018)
Rhinosporidiosis is primarily an infection of the nose caused by Rhinosporidium seeberi. Other sites that can be involved areconjunctiva, urethra, palate, tongue, epiglottis, larynx, trachea, bronchi, skin, vulva, and vagina. It is endemic in certain parts ofIndia and Sri Lanka. The pathogen is difficult to grow in culture and Hematoxylin and Eosin staining helps in confirmation of theetiological agent. Surgery remains the mainstay of treatment. Here is a report aimed at documenting a 26-year-old female patientwith nasal rhinosporidiosis.